Generation of a mobility device for disabled people drive, using the method of quality function - Contreras Bravo, Leonardo Emiro; Granados, Wilmar Augusto (TECCIENCIA, 2013)
This article shows the selection and development of a design to generate a mobility device for physically disabled people between 8- 15 years with T12 pathologies and comorbidities are not in upper. Begin with obtaining the customer’s requirements, and the transformation of these from the tool called quality function (QFD- Quality Function Deployment) and the use of different assessment methods ending condensing all the various elements for the two parts: the client and the producer. After a quantitatively decipher the qualitative, we proceed to develop a systemic process that generates particular elements to reach the design concrete steps by joining the technical elements and requirements of the client (user). Each design methodology used for the elaboration of the designs is explained briefly. In the final part are done several designs and select a model. Whereby it is the result of quality house in graphical and clear. Also shows which were the characteristics, materials and devices selected by the tool called Quality Function Deployment (QFD) to take them into account in the final design.